A Vision from the Margin: Intersectional Insights on Navigating Diversity in Speech and Language Therapy - Malik, Mariam (J&R Press, 2023)
Over the past few years, discussions regarding diversity with the Speech and Language Therapy profession have intensified. A Vision from the Margin aims to bring together the lived experiences from Black and people of colour who have felt marginalized both during training and as they enter their clinical and/or academic practice. Whilst the issues discussed here are vast, and as such one book can never cover every perspective, this book will play an essential role in starting dialogues relating to issues of diversity, anti-racism and social justice, to name a few, within the profession and beyond. This will be transformative for new and existing practitioners and those who research or work in related fields.